2017
DOI: 10.1177/1073274817729901
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Multifocal Leukoencephalopathy and Monoclonal Antibodies

Abstract: Progressive multifocal leukoencephalopathy (PML) is a viral infection predominantly seen in patients with HIV infection. However, with the increased use of monoclonal antibodies (MAB) for various lymphoproliferative disorders, we are now seeing this infection in non-HIV patients on drugs such as natalizumab, rituximab, and so on. The aim of this article is to review the relationship between the occurrence of PML and MAB used in the treatment of hematological malignancies and autoimmune diseases. Review of arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 79 publications
0
52
0
Order By: Relevance
“…The virus remains latent in the kidneys, lymph nodes, and bone marrow, and relatively well-conserved JCV noncoding control regions (NCCRs) can be detected in the urine of asymptomatic healthy individuals ( 16 ). It has been suggested that the virus transforms into a neurotropic form by gene rearrangement after initial infection under immunocompromised conditions and replicates in glial cells ( 17 ). These NCCR sequences change over the course of active infection and are highly variable between PML patients ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus remains latent in the kidneys, lymph nodes, and bone marrow, and relatively well-conserved JCV noncoding control regions (NCCRs) can be detected in the urine of asymptomatic healthy individuals ( 16 ). It has been suggested that the virus transforms into a neurotropic form by gene rearrangement after initial infection under immunocompromised conditions and replicates in glial cells ( 17 ). These NCCR sequences change over the course of active infection and are highly variable between PML patients ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…These NCCR sequences change over the course of active infection and are highly variable between PML patients ( 16 ). The mechanisms underlying PML development during monoclonal antibody treatment are still poorly understood and may vary among biologic agents ( 2 , 17 ). However, it is suspected that the most important pathogenic mechanisms involved in PML evolution secondary to monoclonal antibody treatment include immunosuppression due to elimination/suppression of B cells, cytotoxic T cells, natural killer cells, and/or T helper cells ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the above studies, none of the patients presented PML, but due to the high death rate, it is critical to keep in mind the possibility of developing PML. However, at this time there are no recommendations to screen patients for JCV 87 .…”
Section: Safety Of Rituximabmentioning
confidence: 99%
“…Rituximab is also used off-label as an immunomodulatory therapy for renal transplant and other autoimmune disorders [22][23][24]. After more than 20 years of use, rituximab is considered a safe and effective immunomodulatory therapy; nevertheless, adverse events have been documented, most notably an increased risk of progressive multifocal leukoencephalopathy (PML) particularly for patients with haematological malignancies [25][26][27]. In contrast, reports of adenovirus disease in patients treated with rituximab are uncommon.…”
Section: Impact Statementmentioning
confidence: 99%